Production and decomposition of mangrove litter in Dompak estuary waters, Tanjungpinang - Sinaga, Henna Canlaris; Lestari, Febrianti; Susiana, Susiana (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2024)
Levels of density, production and decomposition of litter in Dompak Estuary Waters. The aim of this research is to determine the level of density, production and decomposition of Mangrove litter in the Dompak Estuary Waters of Tanjungpinang City. This research was carried out in February - March 2024. In determining the sampling points the researchers used the Purposive Sampling method. Sampling in this research used the line transect method. The results of the research show that the level of mangrove density at station 1 is 1,299 ind/ha in the medium category, station 2 is 599 ind/ha in the rare category and station 3 is 1,666 ind/ha in the dense category. Mangrove cover at station 1. Amounted to 73.83% with medium criteria in the medium category. Station 2. Amounting to 65.60% with medium criteria in the medium category and station 3 amounting to 79.93 with solid criteria in the good category and the production of mangrove litter in Dompak Estuary Waters is 3.09 gbk/m2. With a leaf composition of 7.10 gbk/m2, twigs of 0.48 gbk/m2 and flowers/leaves of 1.69 gbk/m2. Mangrove decomposition at station 1 was 21.74%, station 2 was 29.88% and station 3 was 21.14%.